Systematically Observed Movement Integration in a Low Socioeconomic School District: A Cross-Sectional, Observational Study. Issue 5 (June 2019) - Stewart, Gregory; Webster, Collin A.; Brian, Ali; Stodden, David; Egan, Cate A.; Weaver, R. Glenn
Purpose: To describe teacher's integration of activity into general education classroom time (ie, movement integration—MI). Design: Cross-sectional, observational. Setting: Eight elementary schools in a rural, low-income school district. Participants: Elementary classroom teachers (N = 48). Measure: Classroom teachers were observed using the System for Observing Student Movement in Academic Routines and Transitions (SOSMART) on random, unannounced days during the 2015-16 academic year. Analysis: Descriptive statistics were calculated for the frequency and types of MI being used. Results: Of the 9398 SOSMART scans completed, students engaged in movement in 41.3% of the scans. Student movement was observed to be teacher directed in 14.4% and nonteacher directed in 26.9% of scans. Nonteacher-directed movement consisted mostly of transitions ( M = 99.5%) in which movement occurred as a result of preestablished classroom rules, protocols, and organization. Conclusion: This is one of the first studies to provide objective information about MI. These descriptive data lay the groundwork for future correlational and experimental research that can lead to the development of effective intervention design to increase MI use in schools.